Liquidity Glut and Credit Crunch in the Face of Economic Slowdown: Perspectives of Nepalese Stakeholders - Subba, Suraksha; Pradhan, Sumit (Nepalese Journal of Finance, 2025)
This study examines the liquidity glut and credit crunch in the face of economic slowdown: Perspectives of Nepalese stakeholders. Economic slowdown is the dependent variable. The selected independent variables are government policies, exchange rate volatility, banking sector growth, credit demand, interest rate policies, and consumer confidence. The primary source of data is used to assess the opinions of respondents regarding government policies, exchange rate volatility, banking sector growth, credit demand, interest rate policies, consumer confidence, and economic slowdown. The study is based on primary data of 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of liquidity glut and credit crunch in the face of economic slowdown: Perspectives of Nepalese stakeholders. The study showed a negative impact of government policies on economic slowdown. It indicates that supportive governmental actions or regulations leads to reduce economic slowdown. Similarly, the study showed a positive impact of exchange rate volatility on economic slowdown. It indicates that frequent fluctuations in currency values can disrupt trade, investment, and overall economic stability, leading to an increase in the pace of economic slowdown. Likewise, the study showed a negative impact of banking sector growth on economic slowdown. It indicates that higher the banking sector growth, lower would be the economic slowdown. Further, the study showed a negative impact of credit demand on economic slowdown. It indicates that higher the credit demand, lower would be the economic slowdown. In addition, the study showed a negative impact of interest rate policies on economic slowdown. It indicates that central bank of Nepal should adopt accommodative interest rate policies, such as lowering interest rates during economic downturns to encourage borrowing and spending. Moreover, the study also showed a negative impact of consumer confidence on economic slowdown. It indicates that pessimistic consumer sentiment can contribute to reduced spending and investment, thereby dampening economic activity.